(untitled) (Per Musi, 2024)
This case study examines a learning situation that bridges the gap between environmental education and music education. Starting from the concept of sound ecology, secondary students created soundscapes of ecosystems threatened by climate change and human activities. To achieve this, they conducted research on ten endangered ecosystems and used Audacity software to recreate the three components of the soundscape for each of them: biophony, geophony, and anthropophony. Finally, they developed an interactive map showcasing all the projects and held a public exhibition of their work. The results demonstrated a positive impact on student motivation and a significant enhancement of their environmental competence. Regarding project development, challenges emerged due to variations in students’ competency levels and difficulties in adhering to the initial time schedule. This study also analyzes the strategies employed to address these challenges.